Linguistics, phonetics, and field-work - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1983)
The present, rather loosely structured and causerielike paper is an attempt to summarize some of the reflections, expectations, and frustrations which have marred the author during several years of pendling between instrumental phonetics and theoretical and descriptive linguistics, and during many years of practical field-work. The main emphasis is on the - possibly futile - question: is field-work data likely ever to be of any interest to instrumental phonetics, or vice-versa? No attempt is made to deal systematically with general methodological aspects of field-work (for this reason also, references to the literature on field-work techniques are totally omitted). Moreover, what is said below about conditions to be met in connection with instrumental analysis, will be trivial to most readers. Nevertheless, it may be worth while spelling out what it is that causes field-work activities and instrumental phonetic research to exhibit little or no mutual interaction in contemporary language study.